Did you really mean
(3*22) ÷ (6+[28 - 4^4] )
if so, then
= 66 ÷ [ 6 + [-228] ]
= 66 ÷ (-222)
= -66/222
= 11/37 or
= .297297297... notice the repeating sequence 297
how do i simplify (3*22)divided by 6+[28-(4)^4]=? the answer i came up with was 23.
5 answers
(3*22)/6+[28-(4)^4] = -217
(3*22)/(6+[28-(4)^4]) = -11/37
How did you get 23?
4^4 = 256, not 16
2^4 = 16
(3*22)/(6+[28-(4)^4]) = -11/37
How did you get 23?
4^4 = 256, not 16
2^4 = 16
that isnt even one of my options sorry my hw says 23 32 46 or 55
Unless you re-type the question using proper brackets to establish the order of operation, you should not expect either Steve or myself to guess what you meant.
Notice we both took different interpretations of your questions.
Notice we both took different interpretations of your questions.
The rule below shows how to find the distance traveled of an object thrown downward with initial velocity of 3 feet per second. Which answer expresses that rule in the form of an equation?
Square the input and then multiply it by 16. Add this product to the initial velocity multiplied by the input.
Square the input and then multiply it by 16. Add this product to the initial velocity multiplied by the input.